Work–life balance of professional women in rural Spain - Baylina, Mireia; Garcia-Ramon, Maria Dolores; Porto, Ana Maria; Rodó-de-Zárate, Maria; Salamaña, Isabelle; Villarino, Montserrat (Gender, Place and Culture, 2017)
In some regions of Spain, well-educated women decide to move to the countryside to carry out their professional activities. This is a new phenomenon after many decades of female outmigration that also occurs in other European regions. Our aim is to explore how these professional women who decide to live in the countryside manage their work–life balance in this changing space. Our hypothesis is that these women, with high level of education and urban experience are more aware of gender inequality, have greater bargaining power, and therefore, achieve better work–life conciliation with their male partners. Research has been conducted through 60 in-depth interviews with women that have been analyzed through discourse analysis. The results show a complex situation. While these women are building the new ruralities with their work, skills, and insights, social norms concerning family responsibilities move more slowly. The research evidences aspects related to women’s well-being as well as brings the broad issue of care at the center of the feminist debate. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Number: 1
Keywords: 2000 à aujourd'hui; 2010-2019; care; conciliation famille-travail; division sexuelle du travail; espagne; europe; famille; milieu rural; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail